2012
DOI: 10.1007/s11934-012-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prostate Biopsy on Urinary Symptoms, Erectile Function, and Anxiety

Abstract: Transrectal ultrasound-guided prostate needle biopsy (PB) is considered the gold standard for the diagnosis of prostate cancer. Recently, lower urinary tract symptoms and erectile dysfunction have been reported following PB. We reviewed the literature on PB and these symptoms and summarized known findings between these conditions and other variables, such as periprostatic nerve block, saturation biopsy, serial biopsies, and psychological factors associated with PB and cancer. A PubMed search was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…Significant anxiety regarding the possibility of cancer may also have an impact on erectile function. One study found a reduction in all IIEF domains only among men diagnosed with prostate cancer on biopsy, while no significant decrease was found in their counterparts with negative biopsy results 22 28 . Another prospective AS study of 342 patients undergoing TRUS-PB found that EF decreased by 1-point every year for the first 4 years 33 .…”
Section: Erectile Dysfunctionmentioning
confidence: 97%
See 2 more Smart Citations
“…Significant anxiety regarding the possibility of cancer may also have an impact on erectile function. One study found a reduction in all IIEF domains only among men diagnosed with prostate cancer on biopsy, while no significant decrease was found in their counterparts with negative biopsy results 22 28 . Another prospective AS study of 342 patients undergoing TRUS-PB found that EF decreased by 1-point every year for the first 4 years 33 .…”
Section: Erectile Dysfunctionmentioning
confidence: 97%
“…Prostate volume, in particular the transition zone volume, is a well-documented and significant factor associated with subjective voiding impairment and acute urinary retention in most studies 22 . For example, in 5802 men from the Rotterdam section of the ERSPC, prostate volume, transition zone volume/total prostate volume ratio, and a higher IPSS score were all predictors of urinary retention 11 .…”
Section: Lower Urinary Symptoms and Acute Urinary Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with short-term exacerbation of urinary symptoms and erectile dysfunction, as well as anxiety over the procedure [30].…”
Section: Discussionmentioning
confidence: 99%
“…Few data with conflicting opinions [7][8][9] have been reported in literature about the prevalence of ED in men under AS and about its correlations with comorbidity; aim of our study is to evaluate this evenience in our experience and to determine the variables that promote the onset of ED.…”
Section: Introductionmentioning
confidence: 96%